Pengembangan Video Pembelajaran Digital untuk Meningkatkan Kemampuan Berpikir Kritis - Rus Septi; Aryo Andri Nugroho; Bagus Ardi Saputra (Perkumpulan Kualitama Edukatika Indonesia, 2022)
This research and development is motivated by learning during the covid19 pandemic. The learning media available at SD Negeri Dlisen 01 are still less interactive and do not take advantage of technological advances. To overcome this, it is necessary to develop a Digital Learning Video to Improve Critical Thinking Skills in Flat Shape Materials. The purpose of this development research is to describe the critical thinking skills of class IV flat-building material at SDN Dlisen 01, Limpung District which is feasible and valid, effective and practical. The benefits of developing digital learning media to improve critical thinking skills for Grade IV flat building materials at SDN Dlisen 01, Limpung District. This study uses the ADDIE development research model and design with 5 steps, namely analyzing (analyzing), designing (designing), developing (developing), implementing (implementing), and evaluating (evaluate). The results of student learning research proved valid with validity results (88 ,68%). Digital learning video media is effective for improving critical thinking skills of sig value. (2- tailed) of 0.000. This value is smaller than the significance level or <0.05. The results of the student questionnaire showed 84.5% stated that it was easy to use and easy to understand. The results of the field practitioner's questionnaire stated that 92.6% was very interesting and practical to use. The increase in critical thinking skills can be seen in the average results of students from 54 to 84.